PELAKSANAAN STANDAR OPERASIONAL PROSEDUR RESERVASI DI RESTORAN SAFFRON BANYAN TREE BINTAN KEPULAUAN RIAU - Winarsih, Septiani; Sulistyani, Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Restaurant is a building that provides food and drink. Especially in a hotel, restaurant is one of the partthat adds a lot of hotel revenue.. This research was conducted in Saffron restaurant Banyan Tree BintanHotel & Resorts, Teluk Berembang street, Laguna Bintan, Lagoi 29155, Bintan Resort, Indonesia. Thisrestaurant is chosen as a place of research because they have high reservation. This study aims toknowing how the reservation handling at Saffron restaurant. This research uses qualitative descriptivemethod which is researches tried to describe the real situation by collecting some information andexplain in detail way or make a prediction before. Data collection technique are used with observation,interview and documentation. The observation target of this researce are manager, supervisor andthree of waiters. Based on research that has been done about the reservation then obtained the resultthat the reservation handling in accordance with standart operational procedures.Keywords : restaurant, reservation, Banyan Tree Bintan hotel & resort